EXPERIMENTAL VERIFICATION OF THE LAWS OF MOMENTUM AND ENERGY CONSERVATION IN THE SCHOOL COURSE OF PHYSICS USING COMPUTER SYSTEMS - Dan’kiv, Olesya; Stolyarchuk, Ihor; Holskyi, Vitalij; Pan'kiv, Lyudmyla; Uhryn, Yuriy; Leshko, Roman; Brytan, Viktor; Kuzyk, Oleh (Physical and Mathematical Education, 2024)
Formulation of the problem. Learning motivation is one of the most important aspects that needs attention. The use of traditional teaching methods often reduces the interest of modern pupils in studying physics. The practical research of the laws of conservation of momentum and mechanical energy plays an important role in physics lessons. However, implementing simple experiments to confirm these laws sometimes encounters certain physical problems, in particular, such as the difficulty of determining instantaneous velocity. Traditional measurement methods may not be accurate enough or burdensome for pupils, making it difficult for them to understand basic physical principles. The methodology developed in this work effectively combines a real physical experiment with modern computer technologies and is designed to increase both the effectiveness of learning and pupils' cognitive interest in studying physics.Materials and methods. The research involved the analysis and systematization of scientific publications on the use of modern information technologies (smartphones and computer systems) in physics lessons and at home for performing home laboratory work. We also conducted a survey of physics teachers and students (60 respondents) regarding the possibility and necessity of conducting a physics experiment using a smartphone and computer mathematics systems.Results. A method has been developed for experimentally verifying the laws of conservation of momentum and mechanical energy using computer systems and a smartphone video camera, which consists of video recording of the mechanical movement of the body (in some cases in slow motion), subsequent conversion of the video into a set of jpg format frames, and processing of the resulting drawings using computer systems. The proposed method allows determining the instantaneous velocity of a body up to 60 m/s.Conclusions. The proposed method can be used both in physics lessons and when performing home laboratory work or pupil projects, where there is a need to determine the coordinates, instantaneous velocity, acceleration, momentum, and kinetic energy of a body.
Keywords: learning of physics; law of conservation of momentum; law of conservation of energy; smartphone; computing systems